REFLEXÕES SOBRE O ECLETISMO E SUA INFLUÊNCIA NO SERVIÇO SOCIAL BRASILEIRO NA CONTEMPORÂNEIDADE (REMUNOM, 2024)
REFLECTIONS ON ECCLETISM AND ITS INFLUENCE ON BRAZILIAN SOCIAL SERVICE IN CONTEMPORARY TIMEAbstract The present study aims to reflect on the influence of eclecticism on Brazilian Social Service in contemporary times. The methodology used is based on bibliographical research supported by Marx's Critical Social Theory. It is clear that eclecticism still persists in Social Work in contemporary times, influencing conservative theoretical, methodological and ideopolitical positions both in theoretical production and in the professional dimension of Social Work. In this sense, it is necessary to understand the challenges and opportunities that arise in the contemporary world of the social service profession for professional performance that encompasses the perspective of the social totality. Keywords: Contemporary. Eclecticism. Social service.